The Level of Students' Speaking Anxiety in Academic Speaking Classes at Stkip Muhammadiyah Aceh Barat Daya - Safriza Safriza; Zuhri Efendi (PT PUSTAKA CENDEKIA GROUP, 2026)
Speaking anxiety is a prevalent psychological challenge among English as a Foreign Language (EFL) learners, leading to avoidance of oral participation, hesitation in responding to questions, and fear of negative evaluation. This study aimed to identify and classify the levels of speaking anxiety among students in Academic Speaking classes at STKIP Muhammadiyah Aceh Barat Daya, categorizing them as low, moderate, or high. Using a descriptive quantitative approach, the research involved 30 students from the fourth, sixth, and eighth semesters of the English Education Study Program who had completed Advanced Speaking prerequisites, selected through purposive sampling. Data were collected using an adapted Foreign Language Classroom Anxiety Scale (FLCAS) with 33 statements via Google Forms, and analyzed using frequencies and percentages. Findings showed that 90.0% of students experienced moderate speaking anxiety, 6.7% low anxiety, and 3.3% high anxiety, with a mean total score of 101.93. Item-level analysis revealed the highest anxiety was linked to fear of failing to keep up with lessons and speaking about unprepared material, reflecting test anxiety, while lowest scores related to physical panic symptoms. These findings suggest that most students experienced moderate anxiety, sufficient to hinder participation in speaking activities, highlighting the need for supportive, well-structured speaking instruction.